The Effect of Example Non-Example Learning Using Audio Visuals on Motivation and Learning Outcomes in Sciences - Eka Hendrawan; Abdul Azis; Idawati Idawati (Universitas Muhammadiyah Enrekang, 2023)
This research aims to analyze the influence of non-examples learning using audio visual media on motivation and social studies learning outcomes. The type of research used in this research is quantitative research with an experimental approach to find the effect of certain treatments. The type of experiment used is a nonequivalent type of Quasi Experimental.The data analysis technique uses the Manova test with SPSS version 21 to see the effect of the average value of learning motivation for experimental class students before treatment is 73.00 and the average value of learning motivation for experimental class students after treatment is 90.00. Meanwhile, the average value of learning motivation for control class students before treatment was 67.00 and the average value of learning motivation for control class students after treatment was 83.00. As for learning outcomes, the average value of experimental class before treatment was 67.27 and the average value of learning outcomes the experimental class after the treatment was 83.64, while the results of the descriptive analysis of student learning outcomes showed that the average value of the control class learning outcomes before the treatment was 61.82 and the average value of the control class student learning outcomes after the treatment was 74.55, while the constant value of examples non -examples (X) is 3.643 which states that if the variables Y1,Y2 are equal to zero then the non-examples are 3.642, the Y1 coefficient is 0.043, meaning that every time there is an influence on student learning outcomes of 1%, student learning outcomes have an effect of 0.043(4 %) or vice versa, if student learning outcomes experience a decrease of 1% then student learning outcomes decrease by 0.043(4%), the Y2 coefficient of 0.081 means that every time there is an influence on student learning motivation of 1%, student learning motivation has an effect of 0.081(8%) or vice versa, if student learning motivation decreases by 1%, then student learning motivation decreases by 0.081(8%).